The incidence and risk factors of perioperative cardiac complications in noncardiac major surgery in high-altitude areas: A prospective trial in Tibet autonomous region, China - Zhu, Qianmei; Duan, Hanyu; Liu, Zijia; Li, Yi; Zhang, Yuelun; Labaciren,; Shen, Le; Huang, Yuguang (Frontiers in Cardiovascular Medicine, 2023)
Background The risk of perioperative cardiac complications (PCCs) in patients living in high-altitude areas may increase with more adverse clinical outcomes due to the special geographical environment, which has not yet been studied. We aimed to determine the incidence and analyze risk factors for PCCs in adult patients undergoing major noncardiac surgery in the Tibet Autonomous Region. Methods This prospective cohort study enrolled resident patients from high-altitude areas receiving major noncardiac surgery in Tibet Autonomous Region People's Hospital in China. Perioperative clinical data were collected, and the patients were followed up until 30 days after surgery. The primary outcome was PCCs during the operation and within 30 days after the surgery. Logistic regression was used to build the prediction models for PCCs. A receiver operating characteristic (ROC) curve was used to evaluate the discrimination. A prognostic nomogram was constructed to generate a numerical probability of PCCs for patients undergoing noncardiac surgery in high-altitude areas. Results Among the 196 patients living in high-altitude areas involved in this study, 33 (16.8%) suffered PCCs perioperatively and within 30 days after surgery. Eight clinical factors were identified in the prediction model, including older age (P = 0.028), extremely high altitude above 4,000 m (P = 0.442), preoperative metabolic equivalent (MET) < 4 (P = 0.153), history of angina within 6 months (P = 0.037), history of great vascular disease (P = 0.073), increased preoperative high sensitivity C-reactive protein (hs-CRP) (P = 0.072), intraoperative hypoxemia (P = 0.025) and operation time >3 h (P = 0.043). The area under the curve (AUC) was 0.766 (95% confidence interval: 0.785–0.697). The score calculated from the prognostic nomogram predicted the risk of PCCs in high-altitude areas. Conclusion The incidence of PCCs in resident patients living in high-altitude areas who underwent noncardiac surgery was high, and the risk factors included older age, high altitude above 4,000 m, preoperative MET < 4, history of angina within 6 months, history of great vascular disease, increased preoperative hs-CRP, intraoperative hypoxemia, and operation time >3 h. The prognostic nomogram of this study could help to assess the PCCs for patients in high-attitude areas undergoing noncardiac surgery. Clinical Trial Registration ClinicalTrials.gov ID: NCT04819698.